2010
DOI: 10.1016/j.exer.2010.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Episcleral clearance of sodium fluorescein from a bioerodible sub-tenon's implant in the rat

Abstract: We quantified episcleral drug clearance of sodium fluorescein (NaFl) in rats to examine the hypothesis that there is rapid clearance of episcleral water soluble drugs, and that this rapid clearance may limit the amount of drug that is able to reach the posterior segment from an episcleral location. 2 mm implants containing either 12 or 22 ug of NaFl were manufactured and in vitro release rates were determined. Implants were placed in the sub-Tenon's space and the amount of drug remaining in the conjunctiva/scl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…It was found that in enucleated eyes, substantial concentrations were detected compared with live eyes, pointing to a big role played by dynamic barriers and circulatory systems, in clearing the drug from the episcleral location. These results are further confirmed by studies performed by Chan et al which show a higher role of episcleral clearance than choroidal circulation for a drug delivered from a bioerodible subtenon implant in a rat model [42].…”
Section: Sizesupporting
confidence: 81%
See 1 more Smart Citation
“…It was found that in enucleated eyes, substantial concentrations were detected compared with live eyes, pointing to a big role played by dynamic barriers and circulatory systems, in clearing the drug from the episcleral location. These results are further confirmed by studies performed by Chan et al which show a higher role of episcleral clearance than choroidal circulation for a drug delivered from a bioerodible subtenon implant in a rat model [42].…”
Section: Sizesupporting
confidence: 81%
“…Liposomes are also extensively studied for intravitreal and subconjunctival sustained delivery by many research groups [26][27][28][29][30][31][32][33][34][35][36]. For delivery of therapeutic agents for longer periods in a more controlled manner, solid implants or polymeric films have demonstrated the ability for sustained delivery of agents to the posterior ocular segment [19,[37][38][39][40][41][42][43][44]. Another interesting sustained-release formulation is POT-4 (Potentia Pharma ceuticals, KY, USA), which is a synthetic peptide that reversibly binds complement factor C3 and functions as a complement inhibitor.…”
Section: Sustained Posterior Segment Drug Deliverymentioning
confidence: 99%
“… 21 , 22 However, it is difficult to maintain the sustained drug concentrations at target tissue by single sub-Tenon administration due to the rapid clearance of drug by blood and lymphatic flow. 23 , 24 Thus, development of a sustained release platform using sub-Tenon administration may provide an approach to achieve stable drug concentrations and prolonged drug duration.…”
Section: Introductionmentioning
confidence: 99%
“…Chan et al has shown that >99% of the implanted NaF was cleared by 3 hours, and by episcleral circulation. [118].When animals were euthanized immediately following the administration, the NaF was detectable, indicating that the elimination is occurring by means of the dynamic circulation.…”
Section: Release and Distribution Of Nanocarrier Encapsulated Drugs After Periocular Administrationmentioning
confidence: 99%
“…For delivery of therapeutic agents for longer periods in a more controlled manner, solid implants or polymeric films have been studied. [112][113][114][115][116][117][118][119][120]. Intravitreal delivery of polymeric systems may cause clouding of vision, which is not the case for periocular administration.…”
Section: Sustained Ocular Drug Deliverymentioning
confidence: 99%